PENGARUH JENIS BAHAN ATAP PADA PROSES DESALINASI EVAPORASI AIR LAUT - Novitrie, Nora Amelia; Afiuddin, Ahmad Erlan; Hardiansyah, Rizal (Universitas Nahdlatul Ulama Sidoarjo, 2017)
Sea water treatment technology into freshwater is known as desalination. a desalination technique that is both effective and economical is desalination with evaporation. This study aims to determine the effect of roofing materials on the amount of freshwater products produced. The study was conducted using a miniature evaporative tub that has a roof-like shape. Evaporative tubs measuring 1m x 1m x 0.02m material of laminated wood. 20 liters of brackish water is pumped into the tub. The water in the tub is then closed using a roof designed like a roof made of fiberglass and polycarbonate. Brackish water is left in contact with the sun for 24 hours. As a result of heat transfer from sunlight to evaporation tub, brackish water experiences evaporation. The steam moves upward and is captured by the roof wall then undergoes condensation resulting in fresh water. The conclusion obtained is miniature of evaporative desalination roof using fiberglass material obtained 427 mL result while using polycarbonate material obtained fresh water equal to 136 mL.